(untitled) (Quinto Sol, 2013)
As part of the research project called “School textbooks. Images and representations. The buiding of Patagonia in the school imaginaries. Río Negro and Neuquén (1884-1957)”, we are working upon representations concerning Patagonia in school textbooks either state or religious ones (from the Salesian order), previous and subsequent to the peronist period. Some of the images we have been able to trace in such sources include those of Patagonia as indigenous and deserted, Patagonia as a source of oil, Patagonia as the end of our Homeland, as well as Patagonia for tourists when associated to an Argentinian Switzerland. Such representations were the result of an analysis of geographic, historical and economic contents as found within the texts, either in written language or iconography. This line of work has been followed through the selection, for this paper, of a corpus composed of sixty school textbooks known as Manuales Estrada from such period, bearing in mind that hegemonic government policies gave a crucial importance to the inclusion of certain contents through school textbooks. From a qualitative perspective, we focus on historical, geographical and natural resources contents that allow to identify some elements to define Patagonia’s images, as a central purpose of our research.